The Impact of Using The SIMBA Application on The Management of ZIS BAZNAS Funds in South Tangerang City - Yusrin, Erlin Annisa; Zen, Muhamad (Munazzama: Journal of Islamic Management and Pilgrimage, 2024)
This research focuses on the challenges in the manual management of Zakat, Infaq, and Sadaqah (ZIS) funds, which are slow, inefficient, and prone to errors. By implementing the SIMBA application, it is hoped that there will be increased efficiency, effectiveness, transparency and accountability in the management of ZIS funds at BAZNAS South Tangerang City. This research aims to identify the impacts and obstacles in implementing SIMBA and how these obstacles affect the management of ZIS funds. Using qualitative methods with a descriptive approach, data was collected through observation and interviews with BAZNAS managers. The research results show that SIMBA has positively impacted efficiency and accuracy, as evidenced by the increase in zakat collection from IDR 1,620,378,427 in 2020 to IDR 3,699,508,074 in 2023. However, technical obstacles were also found, such as system errors and inaccuracies in the distribution of funds. This research suggests increasing human resource training and improving systems to overcome these obstacles. Implementing SIMBA is important in improving ZIS fund management, but ongoing technical support is needed.